Novel options for the treatment of castration-resistant prostate cancer - Ohlmann, Carsten-Henning; Merseburger, Axel S.; Suttmann, Henrik; Schilling, David Alexander; Trojan, Lutz; Kempkensteffen, Carsten; Corvin, Stefan; Mathers, Michael J.; Bastian, Patrick J. (World journal of urology, 2012)
Docetaxel had been the only treatment of castration-resistant prostate cancer (CRPC) that demonstrated a survival benefit for the patients. After its approval, no considerable progress has been made for several years until cabazitaxel and abiraterone acetate demonstrated a significant survival benefit in phase III clinical trials. Apart from that several other new drugs appeared including inhibitors of the androgen receptor (MDV3100), endothelin receptor antagonists (atrasentan, zibotentan), bone-targeted drugs (denosumab, Alpharadin) and immunotherapies (sipuleucel-T) capable of improving the prognosis of patients with CRPC. Here, we review the most recent advances in the treatment of CRPC and highlight the most promising new agents currently being investigated in clinical trials.
Published online: 20 November 2011
Gesehen am 26.06.2018